Controversias ante la significación: del formalismo al ritual - Raymundo Mier (Estudios sobre las Culturas Contemporáneas)
The problem of significance arising from its dual characterization has passed through semantics under distinct polemic qualities analyzed in this text.. The pragmatic as an alternative to the difficulties of the semiotic and its particular ulterior developments, has defined the place of significance as a "universe populated by rituals and narrations". The author goes a step further and proposes, echoing Malinowski, the passing from the pragmatic to ethnography: language as pure action; the only act capable of generating and, paradoxically, denying meaning